Disease Avoidance Model Explains the Acceptance of Cohabitation With Bats During the COVID-19 Pandemic - Lundberg, Piia; Ojala, Ann; Suominen, Kati M.; Lilley, Thomas; Vainio, Annukka (Frontiers in Psychology, 2021)
Bats and humans have a close relationship based on cohabitation, with bats taking roost in buildings. It has been suggested that bats function as a reservoir of the SARS-CoV-2 virus that causes the COVID-19 disease in humans. A misconception that bats can spread SARS-CoV-2 to humans may have increased negative emotions toward bats and reduced individuals’ acceptance of cohabitation with bats during the COVID-19 pandemic. By applying the disease avoidance model, we tested whether knowledge about bats would be associated with reduced negative emotions toward bats, which in turn would be associated with increased acceptance of cohabitation with bats. Moreover, we tested whether previous experiences of bats, perceived COVID-19 risk, age, gender and level of education would be associated with negative emotions and acceptance of bats. A quantitative survey (N=577) collected during the COVID-19 pandemic in Finland was analyzed with multiple linear regression. The results supported the disease avoidance model. Negative emotions toward bats reduced the acceptance of cohabitation with bats. However, knowledge about bats was associated with increased acceptance of bats both directly, as well as indirectly, via reduced negative emotions. Moreover, perceived COVID-19 risk was associated with increased negative emotions toward bats, and reduced acceptance of bats. Females were more likely than other respondents to report negative emotions, and reduced acceptance of cohabitation with bats. Prior experience of bats was associated with increased acceptance of bats as neighbors. These findings suggest that COVID-19 pandemic may threaten the existence of bats if no action is taken. The findings highlight the importance of correcting misunderstandings about non-human species as transmitters of diseases to humans.